Water as an object of legal regulation of disposal and protection - Zyhrii, Olha; Vityk, Anastasiia; Kuzmenchuk, Anna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article analyzes and examines the legislative base of water protection and water use regulation in Ukraine. There are a number of problems regarding water supply and water use. It is noted that providing the population with quality drinking water is a complex problem, which includes a number of factors of socio-ecological and economical water supply, territorial and regulatory nature